Study on the Spatial Coupling Coordination of Public Service Facilities Around Large Comprehensive Hospitals in Beijing from a Supply–Demand Perspective - Xiaoqi Wang; Bart Julien Dewancker; Tingting Fang; Yingjie Xu; Hai Wang; Andi Zheng (Buildings, 2025)
With the development of urban construction and the improvement of residents’ quality of life, the focus of governance has shifted to a people-centered approach. In the core area of Beijing, there is a mismatch between the existing large comprehensive hospitals (LCHs) and the current demand for medical technology and services. Therefore, this study focuses on tertiary LCHs in the core area of Beijing from the perspective of supply and demand (SD) and explores in depth the problem of matching the crowd concentration and the SD of the surrounding public service facilities in the process of seeking medical treatment. By comprehensively analyzing the public service facilities within a 15-min walking distance around the hospital and considering demand, supply, and transport factors, this study identifies 15 key indicators, constructs an SD coupling model (SDCM) evaluation system, and systematically evaluates the space of public service facilities around an LCH. The results show that the higher the spatial coupling and coordination of these facilities around the LCH, the more tightly the system is connected, and the more pronounced the coupling effect is in the vicinity of the hospital, which suggests that the hospital has a clustering effect on its radiating area.